ARCHIVISUALTECTURE: INVENTARISASI DAN PENGARSIPAN RANCANGAN GAMBAR LAYOUT TEMPAT IBADAT TRI DHARMA (TITD) DI BALI - Hendrawan, Freddy; Dinata, Ramanda Dimas Surya; Artana, I Wayan Bimaskaran; Dewi, Ni Made Diah Septiani (Universitas Mercu Buana, 2024)
Tri Dharma temples in Bali are spread almost throughout the district to accommodate the religious, social, and cultural needs of the Chinese ethnic group and adherents of the Tri Dharma Religion. In traditional Chinese culture, the concept of cosmology and religion from residential, religious, to monument buildings has a long history. Some Tri Dharma temples in Bali have been around for more than 50 years and have historical value. However, since the beginning of the planning of the establishment/development, TITD in Bali has not had a proper building layout drawing document as an archive or architectural or interior data. Therefore, an effort is needed to inventory and archive the TITD layout drawing data in Bali. The solution to this data inventory and archive is to conduct observations, measurements, and interviews and make technical and graphic drawings by utilizing architectural and graphic softwares (AutoCAD dan Adobe Photoshop). Through this documentation and inventory of architectural drawings, TITD can provide benefits in preserving cultural heritage, recovery and restoration, design references, education and research, security and maintenance.